2018
DOI: 10.1128/jcm.00506-18
|View full text |Cite
|
Sign up to set email alerts
|

Agreement between Parallel Canine Blood and Urine Cultures: Is Urine Culture the Poor Man's Blood Culture?

Abstract: Bloodstream infections are a significant cause of morbidity and mortality in critically ill dogs, but due to cost and difficulties in sample acquisition, blood cultures are infrequently obtained. In ill dogs, urine cultures may be recommended as surrogates for blood cultures. In order to determine the outcome agreement between parallel urine and blood cultures, we retrospectively analyzed parallel blood and urine specimens submitted for culture from dogs at the NC State Veterinary Hospital between 2011 and 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…The yield of positive blood cultures matched our hypothesized proportion of 20%, which was toward the lower end of the range of previously reported literature 3–7,9,11 . Given the low number of submissions and reasons for blood culture that we documented, it is likely that this cohort reflects a highly selected population whereby the diagnosis was obscure, blood culture was thought to be of high yield, or direct culture from the source of infection was difficult.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The yield of positive blood cultures matched our hypothesized proportion of 20%, which was toward the lower end of the range of previously reported literature 3–7,9,11 . Given the low number of submissions and reasons for blood culture that we documented, it is likely that this cohort reflects a highly selected population whereby the diagnosis was obscure, blood culture was thought to be of high yield, or direct culture from the source of infection was difficult.…”
Section: Discussionsupporting
confidence: 78%
“…Routine attainment of blood cultures before commencing antimicrobial therapy is recommended in people with sepsis 1 . Blood culture is useful for identifying infecting bacteria and determining antimicrobial susceptibility to guide antimicrobial escalation or de‐escalation 2,3 . There is no consensus on obtaining blood cultures routinely in companion animals with suspected sepsis, and there is a paucity of evidence concerning their utility.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective study of histopathologically confirmed pyelonephritis in dogs, only 79% of dogs had positive urine cultures. 33 The prevalence of urosepsis may therefore be underestimated if culture-negative dogs are excluded. The current study did not exclude dogs if they had negative culture results, as other compelling diagnostic tests (eg, cytology, diagnostic imaging, intraoperative findings) were supportive of an infection.…”
Section: Discussionmentioning
confidence: 99%
“…Although poor agreement was found between parallel blood and urine cultures overall in 1 retrospective study, blood and urine cultures in 7 of 7 dogs with known urogenital disease were concordant. 33 Acquiring blood cultures, however, may be impractical, technically challenging, and expensive. Furthermore, a positive blood culture is not required for the diagnosis of sepsis, and a negative culture does not rule it out.…”
Section: Discussionmentioning
confidence: 99%